2022
DOI: 10.1021/acs.jpca.2c04941
|View full text |Cite
|
Sign up to set email alerts
|

Exploring s–d, s–f, and d–f Electron Interactions in AgnCe+ and AgnSm+ by Chemical Reaction toward O2

Abstract: We investigate gas-phase reactions of free Ag n Ce+ and Ag n Sm+ clusters with oxygen molecules to explore s–d, s–f, and d–f electron interactions in the finite size regime; a Ce atom has a 5d electron as well as a 4f electron, whereas a Sm atom has six 4f electrons without 5d electrons. In the reaction of Ag n Ce+ (n = 3–20), the Ce atom located on the cluster surface provides an active site except for n = 15 and 16, as inferred from the composition of the reaction products with oxygen bound to the Ce atom as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Ag n + species with n = 8, 10, 14, and 20 are inert, and the reactivity of n = 4 is very low, which is different from previous experimental observations. 36,39,40 3.2 Theoretical structures and electronic properties of Ag n…”
Section: Paper Pccpmentioning
confidence: 99%
See 1 more Smart Citation
“…Ag n + species with n = 8, 10, 14, and 20 are inert, and the reactivity of n = 4 is very low, which is different from previous experimental observations. 36,39,40 3.2 Theoretical structures and electronic properties of Ag n…”
Section: Paper Pccpmentioning
confidence: 99%
“…35,38,39 A recent experiment using an ion trap running at room temperature showed that the even-odd oscillation in the reactivity of Ag n + ends at n = 10, and all larger sizes are highly reactive. 40 In these previous experiments, cluster etching paths and reactive odd sizes of Ag n + are hints that extra energies could be ubiquitous in reaction systems, facilitating the crossing of barriers associated with bond breakages or spin accommodation requirements. The reactivity of clusters under relatively violent conditions could partially mask the effects of their intrinsic geometric or electronic characteristics.…”
Section: Introductionmentioning
confidence: 96%
“…Hydrogen storage is an additional compelling topic for study using experimental cluster models combined with theory, as in studies reported by Poutsma et al and Lushchikova et al These studies can be further extended with pure DFT calculations that consider the impact of doped clusters as reported by Charkin et al in which the location-dependent activity of the dopant atom can be explored. A recent experimental study on O 2 reactions with lanthanide-doped Ag n + clusters reported by Arakawa et al might inspire theoretical activity on the role of the close-lying 4f, 5d, and 6s electrons on lanthanides in cluster reactivity.…”
mentioning
confidence: 98%